Properties of Separation Axioms in Bitopological Spaces - Roshmi, Rupaya; Hossain, MS (Journal of Bangladesh Academy of Sciences, 2020)
In this paper, three notions of separation axioms in bitopological space are discussed. Some relations of topology and bitopology in such notions have been found. Further, that these notions are hereditary and topological property are proved. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 191-195, 2019